Sistema de control de contenidos de los micrositios de las unidades académicas de la ESPAM MFL - Rivera Fernández, Williams Ricardo (2018)
The following work had as objective the elaboration of a content control system of the microsites of the academic units at ESPAM MFL that would allow to show, update and modify all type of information that is handled in the institution, whether galleries, events, news, projects, work team. The agile SCRUM methodology was used, which provides the necessary guidelines for the development of applications and consists of three phases. The first phase is the iteration planning, which includes the collection of the functional requirements of the system applying the IEEE 830 standard, the cases of use were also designed and the sprints that define the functional structure of the system from the point of view were planned from the user´s point of view. In the execution phase, we proceeded with the development of the web system: using the PHP technology tool with the Laravel development framework, with the MySQL database manager. In the last phase of inspection and adaptation, the respective delivery of the documentation was made, as is the user and programmer's manual, with the system completed based on the requested requirements.